Decentralization, Democracy and Local Governance - Salvador, Alma Maria O (Archīum Ateneo, 2010)
Primarily a textbook for a course on the Philippine Constitution, a subject constitutionally mandated to be taught in all educational institutions of higher learning. The book is recommended for use in any Philippine politics course, or any course where background on Philippine politics is required.